The Development of Supervision Model to Enhance Research Competencies of Basic Education Teachers in Thailand: The Incasing of the Chonburi-Rayong Secondary Educational Service Area Office - Laksanasut, Saharat (International Journal of Sociologies and Anthropologies Science Reviews, 2022)
This study used the Research and Development (R&D) design to develop a supervision model and investigate its effects on the research competencies improvement of basic education teachers in Thailand. Sixty-seven teachers and educational personnel from Angsilapittayakom School, which is part of the Chonburi-Rayong Secondary Educational Service Area Office, were chosen as the study’s samples using the volunteer sampling method in the academic year 2021. The findings revealed that the investigation and analysis of teachers’ needs were carried out during the early stages of developing a supervision model and that 92.14 percent of the samples had difficulty determining their research problems. The researcher synthesized and developed the "SAHARAT Supervisory Model." There were 7 cyclic steps as follows, 1) Strength Relationship, 2) Attainments of Research, 3) Head-together Plan, 4) Audit of Classroom and Research, 5) Reflection Conference, 6) Award and Reinforcement, and 7) Trumpet the Best Practices. According to expert and specialist evaluations, the supervision model synthesized and developed by the researcher received the highest level of appropriateness and was deemed suitable for use. According to the effects of using the developed supervision model on teachers’ research competencies, at a.01 level of statistical significance, the samples’ research competencies level after the implementation of the SAHARAT Supervisory Model was higher than the research competencies level before the implementation. Taking into account the satisfaction of the overview samples with the SAHARAT Supervisory Model, the overall sample satisfaction with the researcher-synthesized supervision model was at the highest level. The findings of the study will be used as a guideline for educational supervision, with an emphasis on improving teachers’ research competencies.